An Update on Hypomagnesemia and Hypermagnesemia - Steven Van Laecke (MDPI AG, 2023)
Magnesium is an essential element with a pleiotropic role in human biology. Despite tight intestinal and renal regulation of its balance, insufficient intake can finally result in hypomagnesemia, which is a proxy of intracellular deficiency. Conditions such as diabetes, cancer, and infections are often associated with hypomagnesemia, which mostly predicts an unfavorable outcome. The effects of hypomagnesemia can either be direct and include neurological and cardiovascular symptoms or indirect, taking a mechanistic role in inflammation, endothelial dysfunction, and oxidative stress. The indication for intravenous magnesium as a treatment of torsades de pointes and pre-eclampsia is unrefuted, but new indications of peroral or intravenous supplementation, albeit with less supporting evidence, have emerged suggesting, respectively, an attenuation of vascular calcification in chronic kidney disease and improved rate control in atrial fibrillation. Other potential beneficial properties of magnesium, which were claimed by observational data, such as lipid lowering and renal protection, were not, or only partially, investigated in randomized controlled trials. Thus, the role of peroral supplementation of mild chronic asymptomatic hypomagnesemia should be separated from the more targeted prescription of magnesium in specific study populations. (Severe) hypermagnesemia is potentially life-threatening and occurs almost uniformly in subjects with severe renal failure exposed to either supplements or to magnesium-containing cathartics or antacids. Moderate hypermagnesemia is very common in pre-eclamptic women treated with intravenous magnesium. For most (but not all) studied endpoints, mild hypermagnesemia yields a survival benefit. Long-lasting concerns about the potential negative effects of mild hypermagnesemia on bone physiology and structure have so far not been unequivocally demonstrated to be troublesome.